A part of the shikhara of the original temple - Temples of India Project Team (Jio Institute, 2024)
Broken fragments and debris from the original temple assembled on the north face of the adhisthana. Most fragments assembled here were once part of the shikhara of the original temple, other subsidiary structures, and associated parts like the urushringa (subsidiary tower projecting from the sides of the main shikhara). The original shikhara was destroyed and replaced by a circular dome at a later period.